Implementation of E-Learning in Learning Management Education Innovation During The Covid-19 Pandemic - Connie Connie; Eko Risdianto; Meizul Zuki; Adi Asmara (Tadbir : Jurnal Studi Manajemen Pendidikan, 2021)
This study aims to see the effectiveness of e-learning implementation and student responses to e-learning during the Covid-19 pandemic on learning innovation management in education. The sample data in this study were 21 students. The instrument used in this study was a student response questionnaire sheet consisting of 15 items. The results of this study indicate that the instruments used were valid and reliable. This was evidenced by the results of the validity calculation which states that 15 questions were valid and no questions were issued. And also for the results of data reliability calculations using the Cronbach alpha method with a score of 0.88, this value was greater when compared with the rtable value for α = 0.05, namely 0.4329. So it could be said that the data used was reliable. For the results of the analysis with the Rasch model assisted by the Winstep application, it was found that the quality of the questionnaire responses to E-Learning g on innovation and educational management materials at MAP Bengkulu University was very good. From the pairing T-test also obtained SIG <0.05, which means that there was a significant difference.